2016
DOI: 10.1097/brs.0000000000001887
|View full text |Cite
|
Sign up to set email alerts
|

Braces for Idiopathic Scoliosis in Adolescents

Abstract: A Cochrane Systematic Review OBJECTIVE.: To evaluate the efficacy of bracing for adolescents with AIS versus no treatment or other treatments, on quality of life, disability, pulmonary disorders, progression of the curve, psychological and cosmetic issues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 70 publications
1
44
0
1
Order By: Relevance
“…Treatment of AIS with a rigid brace, the most common nonoperative treatment for the prevention of curvature progression, is indicated for a defined group of patients based on their age, sex, magnitude of the curve, and pubertal status. 6,12,17,18 The Chêneau brace, which is intended to de-rotate the apical segment of the curve and provide a 3D correction of the spinal deformity, 19 is the most widely used rigid thoracolumbosacral orthosis in Europe.2 The major mechanism of this orthosis is 3D correction of the spinal deformity through a system of multipoint pressure zones and expansion chambers.2,10 The Chêneau brace creates pressure on the convexity of a curve, and on the opposite side are wide expansion chambers in the frontal, sagittal, and horizontal planes. 9 Regarding the outcomes of brace application, the Chêneau brace has been found to prevent curve progression and to decrease axial rotation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of AIS with a rigid brace, the most common nonoperative treatment for the prevention of curvature progression, is indicated for a defined group of patients based on their age, sex, magnitude of the curve, and pubertal status. 6,12,17,18 The Chêneau brace, which is intended to de-rotate the apical segment of the curve and provide a 3D correction of the spinal deformity, 19 is the most widely used rigid thoracolumbosacral orthosis in Europe.2 The major mechanism of this orthosis is 3D correction of the spinal deformity through a system of multipoint pressure zones and expansion chambers.2,10 The Chêneau brace creates pressure on the convexity of a curve, and on the opposite side are wide expansion chambers in the frontal, sagittal, and horizontal planes. 9 Regarding the outcomes of brace application, the Chêneau brace has been found to prevent curve progression and to decrease axial rotation.…”
mentioning
confidence: 99%
“…Treatment of AIS with a rigid brace, the most common nonoperative treatment for the prevention of curvature progression, is indicated for a defined group of patients based on their age, sex, magnitude of the curve, and pubertal status. 6,12,17,18 The Chêneau brace, which is intended to de-rotate the apical segment of the curve and provide a 3D correction of the spinal deformity, 19 is the most widely used rigid thoracolumbosacral orthosis in Europe.…”
mentioning
confidence: 99%
“…The extensive practice in the last six decades on bracing for scoliosis did not lead to wide consensus in approach and method [1,2]. And the results showed poor in terms of correction.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of orthotic treatment is to stop or slow down the progression of the spinal curvature prior to skeletal maturity, in order to avoid surgery. Orthotic treatments are widely used for progressive curves; their effectiveness have often been questioned [3,4], but a recent by Weinstein et al [5] showed that bracing could significantly reduce scoliosis progression, especially in those patients with high level of compliance to brace wear.…”
Section: Introductionmentioning
confidence: 99%